Investigation of the properties of conventional concrete with addition of waste tire and metakaolin (Research, Society and Development, 2021)
The tire, being essential for the activities of modern life, has become one of the most consumed products in the world and one of the most problematic residues due to its difficult decomposition in nature. Due to this, a solution to the problem is the use of tire waste to replace sand in the composition of concrete, which can be an alternative for the sustainable development of the civil construction sector. Through the ABCP/ ACI method, the specimens were molded with a trace of 1.29: 2.28: 0.5 and their results showed that the compressive strength decreased with increasing percentage of tire waste. However, the specimens added with 15% metakaolin showed an increase in compressive strength with the increase in the percentage of tire residue. He also observed that the water absorption values decreased from the REF-15M sample to the sample with 15% RP-15M. In addition, there was also an increase in water absorption in the absence of metakaolin samples for samples with the addition of 15M metakaolin.